2012
DOI: 10.1002/chem.201103378
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Activation Sequence of Ferrociphenol Anticancer Drug Candidates

Abstract: The complete oxidation sequence of a model for ferrociphenols, a new class of anticancer drug candidate, is reported. Cyclic voltammetry was used to monitor the formation of oxidation intermediates on different timescales, thereby allowing the electrochemical characterization of both the short-lived and stable species obtained from the successive electron-transfer and deprotonation steps. The electrochemical preparation of the ferrocenium intermediate enabled a stepwise voltammetric determination of the stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 36 publications
9
84
1
Order By: Relevance
“…Jurkat cells (4×10 4 per well) were seeded in PBS/10 mM glucose. After 1 h cells were loaded with 1 μM CM-DCFH2-DA and with increasing concentrations of the compounds.…”
Section: Ros Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Jurkat cells (4×10 4 per well) were seeded in PBS/10 mM glucose. After 1 h cells were loaded with 1 μM CM-DCFH2-DA and with increasing concentrations of the compounds.…”
Section: Ros Formationmentioning
confidence: 99%
“…For this reason, the unusual mechanistic properties of organometallic medicinal chemistry are presently the subject of an exponentially growing number of studies [1]. These entities offer inventive strategic approaches [2][3][4][5][6] in terms of optimized space filling, intracellular redox behavior and antitumoral activity, with pharmacophores possessing varied and multiple targeting options that make it possible to counteract the phenomena of resistance to proapoptotic stimuli [7]. To that can be added the variety of available metals [2] and, for the transition elements, the potential availability of several degrees of oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…22 However, the ferrociphenol FC3 (Figure 1), resulting from replacement of a phenyl group of hydroxytamoxifen with a ferrocenyl moiety, displays a dramatic improvement in cytotoxicity toward MDA-MB-231 cells (IC 50 = 0.5µM). 14 Ferrociphenols (FCs, Figure 1) are easily oxidized at relatively low redox potentials, with formation of the corresponding quinone methides (QMs, Figure 1), 23,24 and it was recently shown that these reactive compounds are formed as a result of FC metabolism by liver microsomes, 25 and could play a role in the antitumor properties of FCs. The aim of the work described herein was to study the metabolism of FCs by liver microsomes to determine whether some metabolites are cytotoxic toward MDA-MB-231 breast cancer cells, and, in a more general manner, to potentially find new molecules that are cytotoxic toward hormone-independent breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58][59] They also possess an electrochemically oxidizable Fe (II). 48,60,61 However the 3-carbon ansa derivative 1b remains more active on MDA-MB-231, as well as on the NCI-60 cell lines, 38,45,46 than the acyclic form. 38,46 In the case of the ansa derivative we were unable to characterize or isolate a species of the quinone methide type 60 suggesting that the oxidized form is more active and less stable than in the acyclic series.…”
Section: Discussionmentioning
confidence: 98%